Gendered impacts of COVID-19 on cross-border fish traders in Malawi and Zambia - Mudege, Netsayi; Chepchirchir, Ruth; Kakwasha, Keagan (WorldFish, 2024)
This policy brief is based on a comprehensive study conducted in Zambia and Malawi to understand the gendered impacts of COVID-19 on informal cross-border fish trade. The study demonstrates the disproportionate effects of the pandemic on female traders. Measures implemented to mitigate the health impacts of COVID-19 exacerbated existing gender disparities, imposing heightened obstacles such as restricted mobility and increased market barriers for women. Gender emerges as a pivotal mediator, shaping responses to the pandemic’s impacts and accentuating unique challenges for women in this sector. The study advocates for targeted investments to promote gender equality and resilient value chains, emphasizing the need for tailored strategies that address specific challenges that female traders face.